1974
DOI: 10.1111/j.1600-0765.1974.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plasma and serum on the chemotactic response to plaque

Abstract: The chemotactic response of human PMNL cells to: 1) normal plasma or serum, 2) heat inactivated plasma or serum, 3) autologous plaque mixed with saline, 4) autologous plaque mixed with a complement source (plasma or serum), and 5) autologous plaque mixed with heat inactivated plasma or serum was examined using the Boyden chamber technique. The results indicated serum to be more chemotactic than plasma but that the chemotactic properties of both were heat labile. The addition of autologous plasma to plaque enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The presence of serum inhibitors of chemotaxis shown here in patients with advanced periodontal disease and earlier in several apparently healthy subjects (Mary & Folke 1975) raises speculation on whether certain levels of inhibitor create predisposition to accelerated periodontal deterioration should a lapse in oral hygiene ensue.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The presence of serum inhibitors of chemotaxis shown here in patients with advanced periodontal disease and earlier in several apparently healthy subjects (Mary & Folke 1975) raises speculation on whether certain levels of inhibitor create predisposition to accelerated periodontal deterioration should a lapse in oral hygiene ensue.…”
Section: Discussionmentioning
confidence: 77%
“…The preliminary investigation by Miller, Umana & Folke (1971) suggested that patients with advanced periodontal disease display an impaired leukocyte-chemotactic response to their own dental plaque. Defective chemotactic response, related to cellular dysfunction has also been associated with rheumatoid arthritis (Mowat & Baum 1971a), recurrent infections (Clark et al, Steerman et al 1971) and diabetes mellitus (Mowat & Baum 1971b), Furthermore, serum proteins capable of neutralizing chemotactic factors are present at low levels in normal sera (Barenberg & Ward 1973), and elevated in patients with cirrhosis (Dimeo & Anderson 1971), recurrent infections (Smith et al, 1972), chronic pulmonary emphysema (Ward & Talamo 1973) and glomerular nephritis (Gewurz et al 1968), Impaired chennotaxis may be of significance in patients with advanced periodontal disease as well.…”
mentioning
confidence: 99%
“…A serum factor, believed to be an antibody, which interfers SELA, ROSEN MANN, SCHECHTERAND BOSS Table 2 Mean scores of gingivitis related to experimenlal procedure, interval between challenges and number of iotragingival injections with the development of delayed and Arthus hypersensitivity,, is produced in hyperimmiinized mice (Crowle & Hu 1968). The chemotactic response of neutrophils is antagonized by a plasma factor which has not yet been identified (Mary & Folke 1975). The chemotaxis of mononuclear cells is inhibited by alpha-2-macroglobulitt (Gallin & Kaplan 1974).…”
Section: Discussionmentioning
confidence: 99%